What You Always Wanted to Know about Bohmian Mechanics but Were Afraid to Ask - Passon, Oliver (Technische Universität Dortmund, 2006)
Bohmian mechanics is an alternative interpretation of quantum mechanics. We outline the main characteristics of its non-relativistic formulation. Most notably it does provide a simple solution to the infamous measurement problem of quantum mechanics. Presumably the most common objection against Bohmian mechanics is based on its non-locality and its apparent conflict with relativity and quantum field theory. However, several models for a quantum field theoretical generalization do exist. We give a non-technical account of some of these models.
Physics & Philosophy ; 3
Keywords: Bohmian mechanics; de Broglie-Bohm theory; Interpretation of quantum mechanics; quantum field theory; theory generalization; 100; 530